Households' Risk Management and Coping Strategies: How do the Poor Respond to Various Idiosyncratic and Covariate Shocks in Pakistan?. (June 2022) - Nigar, Neelum; Qayyum, Unbreen
This study examines poor households' vulnerability to idiosyncratic and covariate shocks in Pakistan. First, it observes households' socioeconomic, demographic, and geographic factors that influence the incidence of shocks. Second, it examines households coping strategies adopted to mitigate the negative effects of these shocks. For this purpose, we have studied the shock patterns in poor households and examined the role of the Benazir Income Support Program (BISP) in protecting these households against various shocks. Results indicate simultaneous exposure of idiosyncratic and covariate shocks to the targeted households. Moreover, with a low level of physical and financial assets owned by these households, they resort to coping strategies which are further damaging in nature. We also analyzed shock coping strategies of the sampled households and found that informal coping mechanisms are more prevalent among the poor households when hit by shocks. We have concluded that BISP is ineffective in protecting households in times of shocks and it is thus suggested that the transfers under this program should be generous in size and responsive to shocks in order to be an effective coping strategy for the poor.